Neuroprotective activity of tecoma stans on cerebral ischemia/reperfusion induced oxidative stress in rats (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2022)
This study was done to test the neuroprotective effects of Tecoma stans against brain ischemia/reperfusion caused oxidative stress in the rats. The global cerebral ischemia was generated in male albino Wistar rats by occluding the bilateral carotid arteries for 30 min followed by 1 h and 4 h reperfusion. The levels of malondialdehyde (MDA), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione-s-transferase (GST), and hydrogen peroxide (H 2 O 2 ) activity, as well as brain water content, were examined at various periods after reperfusion. Ischemic alterations were preceded by a rise in MDA and hydrogen peroxide concentrations, followed by a reduction in GPx, GR, and GST activity. Ischemia-induced oxidative stress was greatly reduced after treatment with T.stans. In the groups pre-treated with methanolic extract (250 and 500 mg/kg, administered orally in single and double doses/day for 10 days), T.stans administration dramatically reversed and restored to near normal levels in a dose-dependent manner. In the ischemia reperfusion animals, T.stans reversed the cerebral water content. The neurodegenaration also confirmed by the histopathological changes in the cerebral-ischemic animals. The findings from the present investigation reveal that T.stans protects neurons from global cerebral-ischemic injury in rat by attenuating oxidative stress.